Phenotypic and functional characterization of aqueous humor derived extracellular vesicles. (March 2023) - Verta, Roberta; Saccu, Gabriele; Tanzi, Adele; Grange, Cristina; Buono, Lola; Fagoonee, Sharmila; Deregibus, Maria Chiara; Camussi, Giovanni; Scalabrin, Simona; Nuzzi, Raffaele; Bussolati, Benedetta
Abstract: Extracellular vesicles (EVs) are double membrane vesicles, abundant in all biological fluids. However, the characterization of EVs in aqueous humor (AH) is still limited. The aim of the present work was to characterize EVs isolated from AH (AH-EVs) in terms of surface markers of cellular origin and functional properties. We obtained AHs from patients with cataract undergoing surgical phacoemulsification and insertion of intraocular lenses (n = 10). Nanoparticle tracking analysis, electron microscopy, super resolution microscopy and bead-based cytofluorimetry were used to characterize EVs from AH. Subsequently, we investigated the effects of AH-EVs on viability, proliferation and wound healing of human immortalized keratinocyte (HaCaT) cells in vitro in comparison with the effect of mesenchymal stromal cell-EVs (MSC-EVs). AH-EVs had a mean size of around 100 nm and expressed the classical tetraspanins (CD9, CD63 and CD81). Super resolution microscopy revealed co-expression of CD9, CD63 and CD81. Moreover, cytofluorimetric analysis highlighted the expression of mesenchymal, stem, epithelial and endothelial markers. In the in vitro wound healing assay on HaCaT cells, AH-EVs induced a significantly faster wound repair, comparable to the effects of MSC-EVs, and promoted HaCaT cell viability and proliferation. We provide evidence, herein, of the possible AH-EV origin from stromal cells, limbal epithelial/stem cells, ciliary epithelium and corneal endothelium. In addition, we showed their in vitro proliferative and regenerative capacities. Highlights: AH-EVs expressed mesenchymal/stem (MCSP, CD29) and epithelial/limbal (EPCAM, CD133-1) markers. These data suggest the possible origin of AH-EVs from limbal stem cells and corneal epithelium. AH-EVs showed fast wound repair on immortalized keratinocytes. AH-EVs promoted immortalized keratinocytes proliferation.